New records of invasive hammerhead flatworms (Platyhelminthes, Geoplanidae, Bipaliinae) from Mexico using a citizen science platform, with an identification key to the species found in North America - De Luna, Manuel; García Barrios, Roberto; Valle, Paola; Boll, Piter Kehoma (Pensoft Publishers, 2022)
We present new records of the invasive hammerhead flatworms Bipalium kewense Moseley, 1878 and Bipalium vagum Jones & Sterrer, 2005 (Platyhelminthes, Geoplanidae, Bipaliinae) from several states in Mexico based on iNaturalist and two vouchered specimens. This represents for Mexico the first review of distribution records of this group and highlights the importance of citizen science in monitoring the distribution of these ecologically important invasive predators. Methods for the collection and preservation of hammerhead flatworms, as well as an identification key, are proposed.